CREATION OF AUTONOMOUS LAW - Vukadinović, Gordana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
Great interest in autonomous law first appears in theory, sociology and anthropology of law, and in legal practice. There have been numerous forms of autonomous law from common law, religious, statutory law, city and earthly law, guild law, autonomous labour law, commercial law to international law. In addition, the theory of law recognizes a number of types of autonomous law such as social, intuitive, living, integration law, etc. Just as there is no generally accepted meaning of the term law, there is not a completely clear and precise meaning of the term autonomous law. Besides the term autonomous law, the term soft law has been more and more in use lately.